Globalization and Knowledge Production in the World: A Critical Analysis of the Place of Africa - Bribena, Kelvin (Journal of Reviews on Global Economics, 2019)
Globalization has impacted unprecedentedly on global knowledge production. The politics of knowledge production has taken a new dimension since the end of the Cold War era in which Euro-American ideals has continued to sweep around the world. The import of this is that there has been universalization of what constitutes knowledge and how it is produced. Development generally is patterned after the with the West as the ideal. Africa, a colonial construct has also been affected by the globalization of knowledge production. This paper adopts the qualitative research methodology with the analysis of extant academic works and other materials to make sense of the situation of Africa in the global politics of knowledge production. The paper notes that while Africa was just wriggling out of throes of colonialism politically and efforts at decolonizing knowledge at infancy, the onset of globalization has confined the continent to the backseat among other continents. It notes further that as a result of this, what constitutes knowledge, how it is produced and accessed in Africa remains Western. As a result of this African development is vainly patterned after her ‘erstwhile' colonial masters. The whole idea of post-colonialism in Africa is misleading and knowledge production with which to forge ahead is perpetually colonial, hence Africa's unhealthy backwardness. The paper recommends that Africa needs not only to decolonise knowledge production but also assert its position in global politics of knowledge production in order to be in charge of its development.